Pietra Ollare: Alpine soapstone vessels in Byzantine Corinth - Valente, Rossana (Journal of Greek Archaeology, 2019)
Pietra ollare is the Italian nomenclature for a grouping of different lithotypes of basic and ultrabasic metamorphic rocks, related to green schist facies, and used in the production of ollae (Latin for ‘cooking pots’). The label pietra ollare is not related to a petrographic stone type classification, but rather encompasses, in archaeological literature, a variety of commodities made in a range of stone types, from soft grey soapstone to pale green coloured lithotypes that are medium to fine in grain, such as serpentinine, chlorite and amphibole schists rocks.